Association Between Scientific Production and Accreditation Validity of Dentistry Programs in Colombia - Castillo-Pedraza, Midian Clara; Palacio-Benavides, Juliana Carolina; Wilches-Visbal, Jorge Homero (Journal of the University of Zulia, 2024)
Introduction: Accreditation is the government-endorsed, nationwide certification granted to programs or universities that meet quality standards. Research is one of the key criteria considered for achieving accreditation. Objective: To determine if there is an association between the scientific production of accredited dentistry programs and the duration of their accreditation in Colombia. Methodology: An analytical and cross-sectional study was conducted. Scientific publications in SCOPUS were counted, and the accreditation duration was obtained from the National Accreditation Council’s website as of 2024. The Spearman correlation coefficient was used for association, and the Mann-Whitney test was used for group comparisons, assuming a significance level of 5%. Results: The accreditation duration of the programs ranged from 4 to 8 years, with the most frequent being 8 years (5 programs) and 6 years (4 programs). There were no significant differences in accreditation duration and scientific production between public and private sector programs. The correlation between duration and production was only significant in private sector programs. Hypothetically, if the universities with the highest production (Antioquia and El Bosque) were to increase their accreditation duration by at least 2 years, the correlation between duration and the number of historical and recent publications would become significant. Conclusion: The association was only corroborated in private sector programs. The fact that the most productive programs have shorter accreditation durations affects the significance of the association.